Augmented Reality in Multicultural Education: Bridging Language and Cultural Barriers through Immersive Tools - Azhariah Rachman; Ravi Dara; Vanna Sok (Yayasan Adra Karima Hubbi, 2025)
Background. The increasing globalization of education necessitates innovative approaches to overcome language and cultural barriers in multicultural classrooms. Augmented Reality (AR) technology offers immersive tools that can bridge these gaps, enhancing both language learning and cultural understanding. Purpose. This study explores the role of AR in multicultural education, specifically how it can facilitate communication and cultural exchange among students from diverse backgrounds. The research aims to evaluate the effectiveness of AR tools in promoting language acquisition and cultural awareness in multicultural educational settings. Method. A mixed-methods approach was used, combining quantitative data from pre- and post-intervention language proficiency tests and qualitative data from student and teacher interviews. The study was conducted in three multicultural schools, involving 200 students and 10 teachers. Results. Results showed that AR significantly improved students' language skills, particularly in speaking and comprehension, and increased their cultural sensitivity. Teachers also reported that AR provided a more engaging and interactive learning experience, fostering a deeper understanding of cultural contexts. Conclusion. The study concludes that AR technology can be an effective tool in multicultural education, facilitating better communication, enhancing language learning, and fostering respect for cultural diversity. Future research should focus on the long-term impact of AR in diverse educational settings and explore how to further integrate AR tools into existing curricula.